(untitled) (Jurnal Komunikasi Pembangunan, 2023)
Pokdarwis as a part of community stakeholders, The community as strategic role development and management of natural and cultural potential in tourist areas to create tourist destinations, especially in Cireundeu Village, located in Cimahi Jawa Barat. Research objective is to find out how the method of communication between Pokdarwis to community and findout the obstacles of communication in running its tourism development program This analysis uses a qualitative method by conducting observations and interviews with informants, consisted from chairperson and member of Pokdarwis and community and using descriptive analysis. The results of the study stated that there had been communication between the Pokdarwis chairperson and Pokdariwis members, Pokdarwis communication with community leaders, for implementing work programs with various formal and informal meetings through online technology media or directly, but the program can be implemented thoroughly if the existence of feedback that is in accordance with the communicator’s procession, obstacles occur not only from internal side but obstacles arise from external side which requires obstacles need to be resolved with external support. The recommendation given by researcher about communication process is an obstacle to implementing programs, also need intervention from external parties (Government) to communicate with Pokdarwis can run according to the vision and mission of Pokdarwis.